PENGARUH KOMPENSASI MANAJEMEN, DAN KESULITAN KEUANGAN TERHADAP TAX AVOIDANCE - Zikri Aidilla Syarli (Universitas Prof. Dr. Hazairin SH, 2021)
This study aimed to examine the effect of management compensation and financial distress on tax avoidance with profitability and company size as a control variable. This research was a quantitative descriptive employed a correlation design. The population were the manufacturing companies listed on the Indonesia Stock Exchange 2018-2020 period. The sample were determined by using puposive sampling method which selected 204 companies as the sample of the study. The data were analyzed by using statistical testing of multple linear regression with a significance level of 5%. The results showed that the managamenet compensation had no effect on tax avoidance while the financial distress have a positive effect on tax avoidance. The profitability of control variables and firm size had no effect on tax avoidance. Thus, it can be concluded that management compensation had no effect on tax avoidance while financial distess had effect on it.